Synthesis, crystal structure and in silico studies of novel 2, 4-dimethoxy-tetrahydropyrimido[4, 5-b]quinolin-6(7H)-ones. Issue 29 (29th June 2022) - Patel, Subham G.; Vala, Ruturajsinh M.; Patel, Paras J.; Upadhyay, Dipti B.; Ramkumar, V.; Gardas, Ramesh L.; Patel, Hitendra M.
Abstract : Single-crystal XRD analysis of 2, 4-dimethoxy THPQs and their relative reactivity with properties were investigated using DFT calculation. Molecular docking studies show they effectively docked with main protease of SARS-CoV-2. Abstract : Herein, acetic acid mediated multicomponent synthesis of novel 2, 4-dimethoxy-tetrahydropyrimido[4, 5- b ]quinolin-6(7 H )-one (2, 4-dimethoxy-THPQs) was reported. Single-crystal XRD analysis of four newly developed crystals of 2, 4-dimethoxy-THPQs and their DFT study were also reported. The structure of all molecules was optimized using DFT B3LYP/6-31G(d) level and compared with the corresponding single-crystal XRD data. As a result, the theoretical and experimental geometrical parameters (bond lengths and bond angles) were found to be in good agreement. Frontier molecular orbital (FMO) and molecule electrostatic potential (MEP) analyses were used to investigate the physicochemical properties and relative reactivity of 2, 4-dimethoxy-THPQs. The formation of strong C–H⋯O and N–H⋯O interaction was investigated by Hirshfeld analysis. Furthermore, electronic charge density concentration in 2, 4-dimethoxy-THPQs was analysed by the Mulliken atomic charges which helps to predict the ability of 2, 4-dimethoxy-THPQs to bind in the receptor. The molecular docking of the crystal structure of 2, 4-dimethoxy-THPQs in the main protease (M pro ) of SARS-CoV-2 suggested that all four 2, 4-dimethoxy-THPQs efficiently docked in M pro . Furthermore, 2, 4-dimethoxy-THPQs with a 3-chloro substitution in the phenyl ring have the highest binding affinity because of the additional formation of halogen bonds and highest dipole moment.